Perceptual adaptation of vowels generalizes across the phonology and does not require local context - Chládková, Kateřina; Podlipský, Václav Jonáš; Chionidou, Anastasia (Journal of experimental psychology. Human perception and performance, 2017)
Listeners usually understand without difficulty even speech that sounds atypical. When they encounter noncanonical realizations of speech sounds, listeners can make short-term adjustments of their long-term representations of those sounds. Previous research, focusing mostly on adaptation in consonants, has suggested that for perceptual adaptation to take place some local cues (lexical, phonotactic, or visual) have to guide listeners' interpretation of the atypical sounds. In the present experiment we investigated perceptual adaptation in vowels. Our first aim was to show whether perceptual adaptation generalizes to unexposed but phonologically related vowels. To this end, we exposed Greek listeners to words or nonwords containing manipulated /i/ or /e/, and tested whether they adapted their perception of the /i/-/e/ contrast, as well as the unexposed /u/-/o/ contrast, which represents the same phonological height distinction. Our second aim was to test whether perceptual adaptation in vowels requires local context. Thus, a half of our listeners heard the manipulated vowels in real Greek words, while the other half heard them in nonwords providing no phonotactic cues on vowel identity. The results showed similar adjustment of /i/-/e/ categorization and of /u/-/o/ categorization, which indicates generalization of perceptual adaptation across phonologically related vowels. Furthermore, adaptation occurred irrespective of whether local context cues were present or not, suggesting that, at least in vowels, adaptation can be based on the distribution of auditory properties in the input. Our findings, confirming that fast perceptual adaptation in adult listeners occurs even for vowels, highlight the role of phonological abstraction in speech perception. (PsycINFO Database Record
Keywords: Humans; Adolescent; Psycholinguistics; Adaptation, Physiological; Speech Perception; lidé; fonetika; percepce řeči; generalizace (psychologie); fyziologická adaptace; psycholingvistika; mladý dospělý; Female; lidé středního věku; Male; Phonetics; mladiství; Generalization, Psychological; Adult; dospělí; Middle Aged; ženské pohlaví; mužské pohlaví; Young Adult